Journalism in Croatia in the Southeast European context: deterioration of the 'professional project'. (1st April 2018) - Helena Popović
Abstract : In this article, journalism is analysed within the theoretical framework of sociology of the professions. It focuses on four 'internal attributes' linked to the 'professional project' and the external relation to the profession of agents involved in the professionalisation process. Based on an analysis of the internal attributes and external agents and using the results of quantitative and qualitative studies on Croatian journalism, the article attempts to analyse these dimensions in a diachronic perspective, with the aim of understanding the current status of the journalist profession in Croatia, and the social, political and economic structures that shape it. It looks at the specificities of the region and the structural changes that occurred in the journalistic field with the dissolution of Yugoslavia and the introduction of a liberal market economy and draws on a survey and focus groups as well as an extensive review of the literature. The conclusion is that the 'professional project' of journalism is undergoing a process of gradual decay.